PENGGUNAANLactobacillus plantarum 1 DALAM PEMBUATANSOYGHURT PROBIOTIK SEBAGAI FILLER PADA COKELAT PRALINE - Rizki Indah Amelia; Yusmarini Yusmarini; Rahmayuni Rahmayuni (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2020)
Mahasiswa Fakultas Pertanian Universitas RiauDosen Fakultas Pertanian Universitas RiauJOM FAPERTA Vol. 7 Edisi 2 Juli s/d Desember 2020The purpose of this research was to obtain probiotic soyghurt made with several strains of the Lactobacillus plantarum 1 combined with Lactobacillus bulgaricus and Streptococcus thermophilusas filler in chocolate praline. The study conducted by using a complete random design (CRD) with combination of four treatments and four replications. The treatment werePKM0= S. thermophilus (3%) + L. bulgaricus (3%) +without L. plantarum 1, PKM1=S. thermophilus (2%) + L. bulgaricus (2%) + L. plantarum 1 RN2-12112, PKM2= S. thermophilus (2%) + L. bulgaricus (2%) + L. plantarum 1 RN2-53, PKM3=S. thermophilus (2%) + L. bulgaricus (2%) + L. plantarum 1 RN1-23121. The data were analyzed by analysis of variance, and then analyzed by duncan new multiple range test (DNMRT) at α=5% level. The result showed that the combination of lactic acid bacteria (LAB) did not significantly affected on acidity (pH),total of LAB, water, ash, fat, protein, and carbohydrate content, butsignificantly affected on total lactic acid. Based upon observations, praline chocolate with treatment PKM1 accordance with SNI standards and somewhat favored by the panelistwhich properties as follow: pH (3,88), amount of lactic acid (1,35%), amount of LAB (9,54 log CFU.ml-1), water content (79,78%), ash (1,43%), fat (1,15%), protein (2,98%), carbohydrate (14,67%), less sweet, sour, and not bitter taste, brown, and yellowish white colour, a distinctive chocolate and slightly sour aroma, with somewhat thick texture. Keywords: soyghurt, L. plantarum 1, praline chocolate